Degradação das terras secas nos sertões de Santa Quitéria e Independência – Ceará: contribuições ao monitoramento ambiental - Silva, Érika Gomes Brito da (2018)
Desertification has advanced over portions of the semiarid region of Ceará, assuming variable intensity, which threatens the sustainability of environmental systems. In this scenario, there is a need for environmental assessment and monitoring of desertification. How to evaluate and monitor areas already affected, or leaning to desertification in Ceará? Among the methodological proposals, the use of indicators has been adopted for the identification of vulnerable areas, with the support of geoprocessing tools. The areas chosen for study were two municipalities located in the semiarid, outback of Ceará: Santa Quitéria, with an approximate extension of 4,261 km2, in the Centre-North backlands; and Independence, located in the Sertões of Crateús, with an area of 3,219 km2. The objective of this study was to evaluate the desertification and degradation of the drylands of the backlands of Santa Quitéria and Independência through biophysical and socioeconomic indicators, with the support of geotechnologies in contribution to the environmental monitoring. The research was structured in three main stages: survey and collection of data and cartographic and tabular information; fieldwork; and treatment and analysis of information in the Geographic Information System (GIS). For the construction of a geographic database of the study areas, they were obtained cartographic data from institutions as the Secretariat of Water Resources (SRH), the Brazilian Institute for Geography and Statistics (IBGE), the State Department of Highways (DER-CE) were used; the municipal mesh, the Institute of Colonization and Agrarian Reform (INCRA) and the Institute for Agrarian Development of Ceará (IDACE); elevation information and creation of a Digital Elevation Model (DEM) in Shuttle Radar Topography Mission (SRTM), radar images, with 90m of spatial resolution. The geomorphological features and the physiognomic pattern of the vegetation cover and land use classes were obtained from the visual and digital interpretation of satellite images by CBERS4, in the 1: 100,000 scale. The spatial analysis was performed in ArcGIS 10.4 software, which allowed the storage and manipulation of data to generate thematic maps, in a scale of 1: 200,000. From a systemic approach, the integrated characterization of the abiotic, biotic and anthropic components allowed the identification of 16 environmental systems and subsystems in the study municipalities. At a later stage, environmental systems were evaluated through the application of two groups of indicators of desertification: geobiophysical and socioeconomic. The geobiophysical indicators were: permoporosity; slope; water erosion; thickness; cover and vegetation stratum; aridity and vulnerability to droughts. The group of socioeconomic indicators analyzed: water abstraction; vegetable extractivism; temporary agricultural production; livestock and land structure. Each indicator was composed of five classes, dispose in values from one to five. The highest value attributed corresponded to better conditions for the conservation of natural resources. The geobiophysical indices of desertification (IGBD) were derived from the arithmetic mean obtained from the sum of values assigned to each indicator, divided by the total number of indicators. The analysis of socioeconomic indicators (ISED) evidenced the direct causes of pressure on the natural resources of the desertification processes in the backlands of Santa Quitéria and Independência. As a result of the evaluation, the environmental systems were classified into three levels of susceptibility: low, moderate and high, represented in the Susceptibility Maps to Desertification. It was concluded that the environmental susceptibility of the environmental systems of Santa Quiteria and Independence to desertification reached two levels of intensity: moderate and moderate to high.